ChemInform Abstract: Hydrogen Peroxide Promoted Mizoroki—Heck Reactions of Phenyldiazenes with Acrylates, Acrylamides, and Styrenes. Issue 33 (27th July 2016) - Lasch, Roman; Fehler, Stefanie K.; Heinrich, Markus R.
Abstract: Hydrogen peroxide is a cheap and widely applicable alternative for the established palladium‐silver(I) system.